2014
DOI: 10.1242/jcs.157669
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-6 promotes neural crest cell detachment via F-actin regulation and influences active Rho distribution during epithelial to mesenchymal transition

Abstract: The epithelial-to-mesenchymal transition (EMT) is a complex change in cell phenotype that is important for cell migration, morphogenesis and carcinoma metastasis. Loss of epithelial cell adhesion and tight regulation of cadherin adhesion proteins are crucial for EMT. Cells undergoing EMT often display cadherin switching, where they downregulate one cadherin and induce expression of another. However, the functions of the upregulated cadherins and their effects on cell motility are poorly understood. Neural cres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Studies on zebrafish Cadherin-6 revealed that while reduced in the midbrain during EMT (as seen for chick Cadherin-6B), Cadherin-6 is present at low levels in hindbrain neural crest cells both prior to and during their delamination/EMT, a pattern also noted for chick Cadherin-6B (our unpublished data). After EMT, however, Cadherin-6 is not observed in migratory neural crest cells but is instead localized to neuroepithelial cells (Clay & Halloran, 2014). This group also went on to demonstrate, through live imaging in Cadherin-6 morphant embryos, that knockdown of Cadherin-6 precludes neural crest cell EMT by inhibiting the apical detachment of neural crest cells from the neuroepithelium (Figure 1b).…”
Section: Cadherin Function In Neural C Re S T Ce Ll On T O G E N Ymentioning
confidence: 90%
“…Studies on zebrafish Cadherin-6 revealed that while reduced in the midbrain during EMT (as seen for chick Cadherin-6B), Cadherin-6 is present at low levels in hindbrain neural crest cells both prior to and during their delamination/EMT, a pattern also noted for chick Cadherin-6B (our unpublished data). After EMT, however, Cadherin-6 is not observed in migratory neural crest cells but is instead localized to neuroepithelial cells (Clay & Halloran, 2014). This group also went on to demonstrate, through live imaging in Cadherin-6 morphant embryos, that knockdown of Cadherin-6 precludes neural crest cell EMT by inhibiting the apical detachment of neural crest cells from the neuroepithelium (Figure 1b).…”
Section: Cadherin Function In Neural C Re S T Ce Ll On T O G E N Ymentioning
confidence: 90%
“…In zebrafish, Cadherin-6 is expressed during EMT but in contrast to the chicken embryos, it plays a positive role on EMT. Delamination of fish cephalic NC cells is done by a retraction of the apical pole of the cells and blebbing towards the extracellular matrix (Clay & Halloran, 2013), zebrafish Cadherin-6 controls the activity of the small GTPase Rho during this process (Clay & Halloran, 2014).…”
Section: Emt and Delamination Of The Cephalic Nc Cellsmentioning
confidence: 99%
“…Intriguingly, a number of functional studies suggest that, rather than maintaining epithelial stability among NC cells, Cadherin-6B in chick and Cadherin-6 in fish are required for cells to lose their epithelial junctional polarity and acquire their motile properties (Park and Gumbiner, 2010;Clay and Halloran, 2014). This effect is mediated in chick by non-canonical BMP signaling and in Zebrafish by controlling Rho GTPase distribution in the cytoplasm.…”
Section: Regulation Of Cadherin Expression During Nc Cell Delaminationmentioning
confidence: 99%
“…This effect is mediated in chick by non-canonical BMP signaling and in Zebrafish by controlling Rho GTPase distribution in the cytoplasm. Both signaling pathways ultimately regulate locally the organization of the actin cytoskeleton and promote polarized actomyosin contraction necessary for disruption of apical cell junctions (Park and Gumbiner, 2010;Park and Gumbiner, 2012;Clay and Halloran, 2014). A possible interpretation of these apparently antagonistic functions is that Cadherin-6B would play a dual role in promoting first cell sorting during NC cell specification and maintain their cohesion until delamination while also activating signaling pathways that would act as a negative feedback loop and set the grounds for future delamination.…”
Section: Regulation Of Cadherin Expression During Nc Cell Delaminationmentioning
confidence: 99%